A novel zebrafish model for intermediate type spinal muscular atrophy demonstrates importance of Smn for maintenance of mature motor neurons. Issue 24 (23rd July 2021) - Tay, Shermaine Huiping; Ellieyana, Erna Nur; Le, Yao; Sarusie, Menachem Viktor; Grimm, Clemens; Ohmer, Jürgen; Mathuru, Ajay S; Fischer, Utz; Winkler, Christoph
Abstract: A deficiency in Survival Motor Neuron (SMN) protein results in motor neuron loss in spinal muscular atrophy (SMA) patients. Human SMN is encoded by SMN1 and SMN2 that differ by a single C6T transition in a splice regulatory region of exon 7. In SMN2, exon 7 is skipped leading to an unstable protein, which cannot compensate for SMN1 loss in SMA patients. The disease severity of human SMA (Types 1–4) depends on the levels of SMN protein, with intermediate levels leading to delayed disease onset and extended life expectancy in Type 2 patients. We used homology directed repair (HDR) to generate a zebrafish mutant with intermediate Smn levels, to mimic intermediate, hSMN2 dependent forms of SMA. In the obtained smnA6T ind27 mutant zebrafish, Smn protein formed oligomers but protein levels dropped significantly at juvenile stages. Motor neurons and neuromuscular junctions (NMJ) also formed normally initially but motor neuron loss and locomotor deficiencies became evident at 21 days. Subsequent muscle wasting and early adult lethality also phenocopied intermediate forms of human SMA. Together, our findings are consistent with the interpretation that Smn is required for neuromuscular maintenance, and establish the smnA6T ind27 zebrafish mutant as a novel model for intermediate types of SMA. As this mutant allows studying the effect of late Smn loss on motor neurons, neuromuscular junctions, and muscle at advanced stages of the disease, it will be a valuable resource for testing new drugs targeted towards treating intermediate forms of SMA.